Implementation and reflection of the ethical principles of sports intangible cultural heritage protection-Takes the case study of Taijiquan, for example - Liu, Yifan (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: At the end of 2015, UNESCO issued the Ethics Principles for the Protection of Intangible Cultural Heritage. The following summer, the Chinese edition was officially published in the Study of National Literature. The "Principles of Ethics for the Protection of Intangible Cultural Heritage" places the community of intangible cultural heritage holders at the center of ethical care, and the relationship between the relevant inheritors, cultural holders, relevant interested individuals and groups has gradually become an issue of attention in research and protection. In 2017, the Implementation of the Opinions on the Inheritance and Development Project of Excellent Traditional Chinese Culture issued by the State Council strengthened the core protection concept of "people-centered" from the national level. China’s sports intangible cultural heritage contains traditional culture and Chinese wisdom and interest, with oral transmission, body teaching, will, heart understanding as the main way of inheritance, with the characteristics of rich content, broad extension and live flow. To further study and implement xi jinping, general secretary of intangible cultural heritage protection important speech spirit, thoroughly implement the law of the People’s Republic of China on intangible cultural heritage "on the implementation of the Chinese excellent traditional culture inheritance development project" sports power construction outline and other laws and policy documents, scientific, orderly and sustainable promote our sports intangible cultural heritage protection and research, inheritance and dissemination. This study takes Taijiquan as the case study, takes ethical protection as the breakthrough point, and takes the cultural resources of sports intangible cultural heritage as the primary productivity, and comprehensively promotes the harmonious development of sports material cultural heritage in China. Methods With the background of sociology, anthropology, martial arts, the protection of sports in the new era, analyzes, investigates, and discusses the historical background, characteristics and problems of the practice and protection. Results: (1) "Experience: Based on Chinese practice with rules to follow". Analyze the origin and application objects of the Ethics Principles of the Protection of Intangible Cultural Heritage, the Intangible Cultural Heritage Law of the People’s Republic of China and other relevant principles (2) "Challenge: some reflections to be improved" 1. Reflect on the research tradition and working methods of sports intangible cultural heritage 2. Explain the ethical issues related to the protection of Taijiquan, Among them, around the participation of Taijiquan people and community, The analysis of the community group and subjects; Around the balance between representative and sharing of intangible cultural heritage of Taijiquan, reflection on the ethical relationship between the subject and various external interests; Centering on the separation of visibility and life change in the protection of intangible cultural heritage of sports of Taijiquan, reflect on multiple ethical issues and the compatibility between individual representatives and group holding in the protection of Taijiquan sports intangible cultural heritage, analysis of other related problems such as specific properties was performed. (3) "Improvement: reflections on the current design" 1. Under the concept of "being created by the people, inheriting and serving the people", the Taijiquan sports intangible cultural heritage protection community constitutes the dialectical unity of group and individual subjectivity. 2. Under the concept of "serving to build a community with a shared future for mankind", the dialectical unity of the ethical relationship between Taijiquan sports intangible cultural heritage protection subjects and various external interests 3. The dialectical unity of Taijiquan sports intangible cultural heritage overlapping multiple ethical problems under the concept of "promoting social harmony and sustainable development". Under the concept of "precise policies and integrated protection and evaluation", the dialectical unity of other related issues such as the specific attributes of the intangible cultural heritage of Taijiquan and sports. Conclusion: 1. Ethics awareness in the protection of Taijiquan sports intangible cultural heritage is still in the preliminary stage of development. Ethical issues that should be considered and paid attention to in the protection work have not been widely publicized to the protection units and individuals at all levels. 2. While making effective publicity, relevant researchers should maintain active communication with protection workers and sports intangible cultural heritage communities, sports intangible cultural heritage holders and inheritors, make timely analysis of practical problems and emerging new ethical phenomena, and actively provide reference suggestions for the protection work. 3. further promotes the transition of ethical protection from representative inheritors of sports intangible cultural heritage to representative inheritance groups. 4. generates an effective and feasible supervision mechanism to supervise the implementation of the ethical principles of sports intangible cultural heritage. It can be generated within the protection unit or entrust independent research institutes to design and execute. If the former, the designated research institution should be assisted as a professional guidance unit. If the latter, regular data shall be provided to the relevant protection unit.